Fate of mercury in two CFB utility boilers with different fueled coals and air pollution control devices. (1st September 2019) - Li, Xinyu; Li, Zhonggen; Fu, Chengcheng; Tang, Li; Chen, Ji; Wu, Tingting; Lin, Che-Jen; Feng, Xinbin; Fu, Xuewu
Highlights: Hg in flue gas out of boiler consisted of 95.11–99.26% Hg p regardless of fuel types. Air pollution control devices can remove >98.53% of Hg in flue gas, mostly by dust collector (>97%) Total Hg in stack gas was low (0.19–0.24 µg·m −3 ) for the two CFB utility boilers. Mercury emission factors of the two power plants were 1.19–1.54 mg Hg·t −1 coal. Abstract: Mercury (Hg) emitted from two circulating fluidized bed (CFB) utility boilers (150 MW, P#1 and 300 MW, P#2) in Guizhou province, Southwest China, was characterized. P#1 used anthracite coal and was equipped with in-furnace desulfurization (IFD) and electrostatic precipitator (ESP). P#2 co-burned gangue and coal slime and was equipped with selective non-catalytic reduction (SNCR), ESP, fabric filter (FF) and limestone gypsum wet flue gas desulfurization (WFGD). Flue gas samples from the inlets and outlets of air pollution control devices (APCDs) in the two plants were analyzed using the Ontario Hydro Method (OHM). Solid samples including feed coal, limestone, bottom ash, fly ash and gypsum were also collected and analyzed. Hg removal efficiency by the APCDs and Hg emission factors (MEFs) were estimated. Total Hg (THg) in the flue gas at the inlet of ESP are 32.3 µg·m −3 and 15.3 µg·m −3 for P#1 and P#2, respectively, both dominated (95.11–99.26%) by the particulate form (Hg p ). THg decreased significantly to 0.19–0.24 µg·m −3 at the final APCDs outlets of these two power plants, yielding an overall Hg removal efficiency of 98.53–99.41% for THg. Mass balance analysis indicated that >97% of Hg in coals ended up in captured fly ash. MEFs of the two tested power plants are relatively lower than the values typically found in CFB and pulverized coal (PC) utility boiler power plants. The emission data of Hg from CFB coal-fired power plants should be updated and attention should be directed to the secondary emission/release of Hg from the captured fly ash.